Porous Lattice Structure of Femoral Stem for Total Hip Arthroplasty - Botello- Arredondo, A. I.; Zúñiga-Aguilar, E. S.; Moya-Bencomo, M. D.; Acosta-Sánchez, L. A. (Revista Mexicana de Ingenieria Biomedica, 2020)
Total Hip Arthroplasty (THA) is one of the surgical procedures carried out satisfactorily in procedures for osteoarthritis and trauma lesions. ATC surgery reduces pain and improves the quality of life of young patients. Therefore, it is of great importance to improve the properties of hip implants, since current implants do not match their lifespan with the life expectancy of a young patient. This is because the solid prostheses that currently exist have a higher Young’s modulus, and therefore are too rigid compared to the bone tissue. On the other hand, the cyclic and continuous loads to which the hip joint is subjected in daily activities, can cause loosening and consequent implant loss The present work proposes an implant manufactured with a porous lattice structure, which aims to reduce stiffness, allow bone growth and a more effective mechanical load transfer. Three computational models subjected to static charges were evaluated and compared: 1) healthy femur, 2) implanted femur with a commercial prosthesis, and 3) implanted femur with a prosthesis with lattice structure. For the computational analysis it was decided to perform a static analysis of a person standing on the left foot; a load equivalent to the body weight was applied on the head of the femur, balancing the reaction forces in the system of forces (contact force, body weight, and abductor muscle).. The results were shown in terms of displacement, compression and deformation. The model implanted with a prosthesis with a lattice design presented a slight decrease in displacement, and a decrease in compression and deformation values, which indicated that the proposed design has a better distribution and transport of the loads through its structure.